Die verhouding tussen onderrig en navorsing in universitêre verband - Rossouw, H. W. (Koers, 2000)
The relationship between teaching and research in the universityThe relationship between teaching and research is one aspect of the current dilemma concerning universities that has increasingly become the topic of debate. Among the uncertainties involved in the situation of the university belongs: an apparent tension between the teaching and research tasks of this institution. The question is whether this tension points to an intrinsic incompatibility of activities that do not really belong together and which consequently cause mutual disruption or whether it is it only a matter of an imbalance between interdependent functions. And if the latter, how can a healthy balance between university teaching and research be theoretically accounted for and practically implemented? The article discusses these questions, and, using the concept of “the academic learning process", argues in favour of the unity between teaching and research in the context of the university.